INFLUENCES OF INCUBATION TIME AND SUCROSE CONCENTRATION ON MICE (Mus musculus L.) OOCYTE VIABILITY FOR ENUCLEATING PROCEDURE - Ekayanti Mulyawati Kaiin; Muhammad Gunawan; Madihah Madihah; Ghina Nafisah (Jurnal Kedokteran Hewan, 2018)
This study aimed to find out the optimum incubation time to complete mouse oocyte maturation at Metaphase II (MII) stage and determine the optimum sucrose concentration enabling to induce nuclear swelling for visualization that is important for enucleating process at the initial procedure of somatic cell nuclear transfer (SCNT). In this current study, mice were used as animal model. Completely randomized design was arranged, consists of 2 trials with 4 treatments and 7 replications. In the first trial, the oocytes were cultured at 0-2, 4-6, 8-10, and 12-14 h in 5% CO2 incubator at 37 C. Second, the MII oocytes obtained from previous trial were cultured in M199 medium containing different concentrations of sucrose (0, 1.5, 3, and 6%). The parameters measured were the oocyte viability at various stages, i.e germinal vesicle (GV), metaphase I (MI), anaphase/telophase I (A/T I), and metaphase II (MII), and the viability of swollen nuclear oocytes using Hoechst/PI staining. The results showed that the optimum incubation time required by oocytes to reach MII stage was 12-14 h with a percentage of 57.14±12.67%, while the optimum sucrose concentration for nuclear swelling was found at 3% with a percentage of 100±0.00%. Our findings provided preliminary results related to the maturation process of the mouse oocyte nucleus, which is meaningful for the initial procedure of SCNT.